ГЕНЕТИЧЕСКИЙ ПОЛИМОРФИЗМ STAT4, PTPN22, VEGF, TGF-B, PDCD1 и PD-L1 у ДЕТЕЙ С ПОЛИКИСТОЗОМ ПОЧЕК - Белькевич, Анна Геннадьевна; Сукало, Александр Васильевич; Козыро, Инна Александровна; Никитченко, Наталья Васильевна; Гончарова, Роза Иосифовна (Children’s Medicine of the North-West, 2021)